2006
DOI: 10.1073/pnas.0606251103
|View full text |Cite
|
Sign up to set email alerts
|

Culling and cattle controls influence tuberculosis risk for badgers

Abstract: Human and livestock diseases can be difficult to control where infection persists in wildlife populations. In Britain, European badgers (Meles meles) are implicated in transmitting Mycobacterium bovis, the causative agent of bovine tuberculosis (TB), to cattle. Badger culling has therefore been a component of British TB control policy for many years. However, large-scale field trials have recently shown that badger culling has the capacity to cause both increases and decreases in cattle TB incidence. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
174
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(186 citation statements)
references
References 26 publications
9
174
1
2
Order By: Relevance
“…The selected nature of the samples of animals examined in these previous studies, and in some cases the small numbers of animals included, may account for differences in values obtained for the proportions of animals showing visible lesions or severe pathology. RBCT findings have shown that the prevalence of infection can differ spatially both at the level of badger social groups and region [19] suggesting that samples of animals drawn from a small number of groups may not be representative of the wider population. We acknowledge three potential sources of bias in the sampling method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected nature of the samples of animals examined in these previous studies, and in some cases the small numbers of animals included, may account for differences in values obtained for the proportions of animals showing visible lesions or severe pathology. RBCT findings have shown that the prevalence of infection can differ spatially both at the level of badger social groups and region [19] suggesting that samples of animals drawn from a small number of groups may not be representative of the wider population. We acknowledge three potential sources of bias in the sampling method.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that such storage may reduce the sensitivity of detecting M. bovis by culture [18]. Analyses conducted using data from proactive areas in the RBCT showed a borderline significant association between being culture negative for M. bovis and having been stored for more than 7 days [19]. As our main interest in these analyses is the pathology in tuberculous badgers and freezing is also likely to have influenced detection of lesions at necropsy, data for all carcases stored for more than 7 days were excluded from the analysis.…”
Section: Necropsymentioning
confidence: 99%
“…Rather, increases occurred at greater distances than we predicted and were sustained up to scales of 4,000 m. Thus, it is perhaps most likely that the few observed excesses of cases represented a statistical artefact, especially in light of the number of comparisons performed when assessing multiple scales. Alternatively, spatiotemporal analyses can be affected by the influence of confounding factors (for a discussion in an epidemiological context, see Wakefield et al 2000). An apparent excess of new problem cases following management action at badger setts could reflect spatial and temporal heterogeneity in phenomena related to badger or human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Selective culling of test-positive cattle has helped to eradicate TB across much of the developed world, but eradication from the United Kingdom is impeded by M. bovis infection in European badgers (Meles meles) (8), as well as by continued transmission among cattle (9)(10)(11). Transmission has also been documented among badgers (12), from cattle to badgers (13), and from badgers to cattle (14,15). Because badgers are clearly a contributing factor to the UK's TB problem, successive TB control policies have included culling of badgers (7,8).…”
mentioning
confidence: 99%